New subcutaneous PowerFlow port results in cost and time‐savings in a busy outpatient apheresis clinic. Issue 4 (12th December 2018) - Williams, Lance A.; Arnesen, Christine; Gunn, Christina; Boshell, Michael N.; Pham, Huy P.; Guillory, Bryan; Adamski, Jill; Marques, Marisa B.
Abstract: Many vascular access options, such as subcutaneous ports, are currently on the market for use in both medication infusion and for procedures, such as therapeutic plasma exchange and extracorporeal photopheresis. We compared the cost and time necessary to complete apheresis procedures using either Angiodynamic's Vortex or Bard's PowerFlow subcutaneous ports by reviewing our experience on two patients undergoing long‐term apheresis treatments with at least 10 procedures with each type of port. We analyzed the cost of needles and thrombolytic therapy, staff time, overall procedure length, and the total time the patient was in the apheresis unit. We also compared flow rates and alarm rates between the two ports. In this small pilot study, use of the PowerFlow port resulted in significant cost and time savings, with mixed results for flow rates. Our results need to be confirmed in a larger patient population prior to recommending wide implementation of Bard's PowerFlow port.